Individual variability in lactate response to cycling prescribed using physiological thresholds and peak work rate: a crossover within-participant repeated measures study - Lauren J. Pacitti; Kaitlyn E. Shikaze; Nia Simpson-Stairs; Jonathan Stringer; Brendon J. Gurd (European Journal of Applied Physiology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Exome-informed formulations of food proteins enhance body growth and feed conversion efficiency in ad libitum-fed mice - Tong Wu; Davaatseren Baatar; Anne E. O' Connor; Moira K. O'Bryan; Jessica M. Stringer; Karla J. Hutt; Minoli Malimige Aponso; Keyne Monro; Jiaqiang Luo; Yingchun Zhu; Andreas Ernst; Elyse O.K. Swindells; et al. (Food Research International, 2024)

Widespread chromosomal rearrangements preceded genetic divergence in a monitor lizard, Varanus acanthurus (Varanidae) - Jason Dobry; Erik Wapstra; Emily J. Stringer; Bernd Gruber; Janine E. Deakin; Tariq Ezaz (Chromosome Research, 2023)
Chromosomal rearrangements are often associated with local adaptation and speciation because they suppress recombination, and as a result, rearrangements have been implicated in disrupting gene flow. Although there is strong evidence to suggest that chromosome rearrangements are a factor in genetic isolation of divergent populations, the underlying mechanism remains elusive. Here, we applied an integrative cytogenetics and genomics approach testing whether chromosomal rearrangements are the initial process, or a consequence, of population divergence in the dwarf goanna, Varanus acanthurus . Specifically, we tested whether chromosome rearrangements are indicators of genetic barriers that can be used to identify divergent populations by looking at gene flow within and between populations with rearrangements. We found that gene flow was present between individuals with chromosome rearrangements within populations, but there was no gene flow between populations that had similar chromosome rearrangements. Moreover, we identified a correlation between reduced genetic variation in populations with a higher frequency of homozygous submetacentric individuals. These findings suggest that chromosomal rearrangements were widespread prior to divergence, and because we found populations with higher frequencies of submetacentric chromosomes were associated with lower genetic diversity, this could indicate that polymorphisms within populations are early indicators of genetic drift.

Climate change research and action must look beyond 2100 - Christopher Lyon; Erin E. Saupe; Christopher J. Smith; Daniel J. Hill; Andrew P. Beckerman; Lindsay C. Stringer; Robert Marchant; James McKay; Ariane Burke; Paul O’Higgins; Alexander M. Dunhill; Bethany J. Allen; et al. (Global Change Biology, 2022)
Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

A Review of Translational Magnetic Resonance Imaging in Human and Rodent Experimental Models of Small Vessel Disease - Michael S. Stringer; Hedok Lee; Mikko T. Huuskonen; Bradley J. MacIntosh; Rosalind Brown; Axel Montagne; Sarah Atwi; Joel Ramirez; Maurits A. Jansen; Ian Marshall; Sandra E. Black; Berislav V. Zlokovic; et al. (Translational Stroke Research, 2021)
Cerebral small vessel disease (SVD) is a major health burden, yet the pathophysiology remains poorly understood with no effective treatment. Since much of SVD develops silently and insidiously, non-invasive neuroimaging such as MRI is fundamental to detecting and understanding SVD in humans. Several relevant SVD rodent models are established for which MRI can monitor in vivo changes over time prior to histological examination. Here, we critically review the MRI methods pertaining to salient rodent models and evaluate synergies with human SVD MRI methods. We found few relevant publications, but argue there is considerable scope for greater use of MRI in rodent models, and opportunities for harmonisation of the rodent-human methods to increase the translational potential of models to understand SVD in humans. We summarise current MR techniques used in SVD research, provide recommendations and examples and highlight practicalities for use of MRI SVD imaging protocols in pre-selected, relevant rodent models.

Extracellular Vesicles Released by Glioblastoma Cells Stimulate Normal Astrocytes to Acquire a Tumor-Supportive Phenotype Via p53 and MYC Signaling Pathways - S. Hallal; D. M. Mallawaaratchy; H. Wei; S. Ebrahimkhani; B. W. Stringer; B. W. Day; A. W. Boyd; G. J. Guillemin; M. E. Buckland; Kimberley L. Kaufman (Molecular Neurobiology, 2019)

Climate change adaptation and cross-sectoral policy coherence in southern Africa - Matthew I. England; Andrew J. Dougill; Lindsay C. Stringer; Katharine E. Vincent; Joanna Pardoe; Felix K. Kalaba; David D. Mkwambisi; Emilinah Namaganda; Stavros Afionis (Regional Environmental Change, 2018)

Soil properties of mangroves in contrasting geomorphic settings within the Zambezi River Delta, Mozambique - Christina E. Stringer; Carl C. Trettin; Stanley J. Zarnoch (Wetlands Ecology and Management, 2016)

Composition, biomass and structure of mangroves within the Zambezi River Delta - Carl C. Trettin; Christina E. Stringer; Stanley J. Zarnoch (Wetlands Ecology and Management, 2016)

The heparan sulfate editing enzyme Sulf1 plays a novel role in zebrafish VegfA mediated arterial venous identity - Bushra Gorsi; Feng Liu; Xing Ma; Timothy J. A. Chico; Ashok Shrinivasan; Kenneth L. Kramer; Esther Bridges; Rui Monteiro; Adrian L. Harris; Roger Patient; Sally E. Stringer (Angiogenesis, 2014)

Learning invariant object recognition in the visual system with continuous transformations - S. M. Stringer; G. Perry; E. T. Rolls; J. H. Proske (Biological Cybernetics, 2006)